The crystal structure of (E)-7-chloro-1-cyclopropyl-6-fluoro-3-((2-hydroxybenzylidene)amino)quinolin-4(1H)-one, C19H14ClFN2O2 - Ibrahim Iman M.; Hasan Kamrul; Ravi Urmila; Al-Qawasmeh Raed A.; Khanfar Monther A. (Zeitschrift für Kristallographie - New Crystal Structures)
C19H14ClFN2O2, triclinic, P1‾$\bar{1}$ (no. 2), a = 8.9893(3) Å, b = 9.5324(3) Å, c = 10.1917(4) Å, α = 95.1780(10)°, β = 96.5320(1)°, γ = 116.3930(10)°, V = 767.42(5) Å3, Z = 2, Rgt(F) = 0.0355, wRref(F2) = 0.0966, T = 100(2) K.